ARTIFICIAL INTELLIGENCE IN AGRIBUSINESS DEVELOPMENT: A LITERATURE REVIEW - Abdul Rochman (Berajah Journal, 2026)
Artificial Intelligence (AI) is increasingly developing as a technology that is able to support the transformation of the agribusiness sector through the use of data and business process automation. This study aims to analyze the opportunities, challenges, and directions of Artificial Intelligence development in agribusiness based on various relevant scientific literature. The research uses the library research  method with data sources in the form of journal articles, books, proceedings, and other scientific publications obtained through documentation studies. The collected data was analyzed using content analysis techniques to identify key themes related to the application of AI in agribusiness. The results show that the use of AI makes a significant contribution to improving production efficiency, optimizing the use of resources, predicting the accuracy of crop yields, supply chain management, and data-driven decision-making. In addition, AI implementation still faces various obstacles, such as limited digital infrastructure, high technology adoption costs, low human resource capacity, and data security and privacy issues. This study also shows that future AI development needs to be directed towards more inclusive, affordable, and sustainable technologies to support the increase in the competitiveness of the agribusiness sector. Thus, AI has the potential to be a strategic instrument in encouraging the modernization and sustainability of agribusiness in the digital era.